Chronic pouchitis and Crohn's disease of the pouch after ileal pouch-anal anastomosis: Incidence and risk factors. Issue 9 (September 2021) - Bresteau, Clément; Amiot, Aurélien; Kirchgesner, Julien; de'Angelis, Nicola; Lefevre, Jérémie H.; Bouhnik, Yoram; Panis, Yves; Beaugerie, Laurent; Allez, Matthieu; Brouquet, Antoine; Carbonnel, Franck; Meyer, Antoine
Abstract: Background: Restorative proctocolectomy with ileal-pouch anal-anastomosis (IPAA) is the operation of choice for patients with ulcerative colitis (UC) or with inflammatory bowel diseases unclassified (IBDU). Aims: to assess the incidence and risk factors of chronic pouchitis (CP) and Crohn's disease of the pouch (CDP) in patients with UC or IBDU. Methods: We conducted a retrospective study. We included consecutive patients who underwent IPAA between 2011 and 2019. The main outcome was the occurrence of CP or CDP. We looked for risk factors with multivariable and a least absolute shrinkage and selection operator (LASSO) Cox models. Results: 247 patients were included. The 5-year cumulative incidence of CP or CDP was 35.3% (95%CI: 26.2–43.2). In multivariable analysis, diagnosis of IBDU, age less than 35 years at surgery and extra-intestinal manifestations other than articular and primary sclerosing cholangitis were associated with higher incidence. The LASSO analysis identified these three prognostic factors and articular manifestations. In patients with two or more prognostic factors, 5-year cumulative incidence, was 65.2% (95%CI: 41.8–79.2). Conclusions: Five years after IPAA, approximately one-third of patients had either CP or CDP. Risk factors were IBDU, an age less than 35 years at surgery, articular manifestations and other extra-intestinal manifestations.